Peran Cryptocurrency Dalam Diversifikasi Portofolio Investasi Di Era Digital - Sulaksana, Dadang; Sumanti, Maya; Veronica; Maryanti (CV. SINAR HOWUHOWU, 2025)
Cryptocurrency has become one of the most attractive investment instruments in the digital era. This article examines the role of cryptocurrency in portfolio diversification using the Modern Portfolio Theory (MPT) approach. This study employs historical data analysis to measure volatility, correlation with traditional assets, and the impact of cryptocurrency integration into investment portfolios. The findings indicate that cryptocurrency has a low correlation with traditional assets such as stocks and bonds, potentially enhancing the risk-return ratio (Sharpe ratio). However, high volatility and regulatory uncertainty pose significant challenges. With an appropriate allocation strategy, cryptocurrency can serve as a complementary asset in portfolio diversification, particularly for investors with a high-risk tolerance.